A Machine Learning Method to improve Supplier Delivery Appointments in Supply Chain Industries - Anitha Palakshappa; Sumana Maradithaya; Charunayana V (Brazilian Journal of Operations & Production Management)
Goal: The paper aims at the customization of supplier schedules upon the priority of key articles. It aims at the prediction of an appointment to a supplier based on the key aspects. The objective of this study is to investigate whether the machine learning algorithms can be used to predict the delivery dates of the products based on the trained data.